KONKRITISASI PRINSIP INTERNASIONAL MINIMUM STANDARD OF CIVILIZATIONDALAM KONSEP PENGUASAAN PERTAMBANGAN DI INDONESIA - Recca Ayu Hapsari (Arena Hukum, 2018)
AbstractMining became an attraction in investing in Indonesia. the concept of mastery of mining in Indonesia in terms of Article 33 paragraph (3) of the NRI Constitution of Year 1945 with a historical approach of legislation and the application of the principle of the Minimum International Standard Of Civilization (IMS) in defining the bargaining position Indonesia as the